Caltrans structural control for bridges in high seismic zones. - Roberts, James E. (Earthquake engineering & structural dynamics.)
The California Department of Transportation has nearly completed a 5.5 billion dollars seismic retrofit program to retrofit strengthen over 2200 bridges on the state highway systems to they conform to the latest seismic hazard and performance criteria. Various unique solutions were developed and implemented to achieve the goals of the program. These techniques included the use of conventional steel and reinforced concrete jackets on bridge columns, advanced fiberglass and carbon fiber composite jackets, seismic isolation bearings and dampers, and seismic isolation silos. All of these techniques were designed to control the performance of a bridge by modifying or tuning its structural characteristics. This is much easier to achieve on a new bridge than on the retrofit of an existing bridge. Ideally a bridge should be designed with no deck joints and no bearings, with monolithic columns to superstructure framing, and with all columns the same length. While this ideal design is not achievable on many bridges, there are modifications that can reduce the vulnerability to damage during an earthquake. The structural control techniques illustrated are: hinge restrainer cables and extenders; fewer deck joints; column and foundation design to control the location of plastic hinge zones; conservative shear key designl; pier rocking; steel jackets and carbon shells for external confinements; seismic isolation silos; shock transmission dampers; rubber-lead core isolation bearings; and inverted pendulum isolation bearings.